Challenges for managing health infodemics in COVID-19 times - Espinoza-Portilla, Elizabeth (2022)
In February 2020, at the time the COVID-19 pandemic was declared, the World Health Organization warned of massive infodemics, that is, a large amount of information that in some cases may be correct (in other cases not), and that may make it difficult for people to find reliable sources and appropriate guidance when required. Infodemics is spreading extremely fast, particularly with the rise of social media. Infodemiology is the science studying the distribution and determinants of information in electronic media, such as Internet, or in a population, for the purpose of informing on public health and public policies. During the period from 2002 to 2021, 484 publications on infodemiology were registered in the MEDLINE database (via PubMed), and 71.9% of the publications (348/484) appeared during 2020 and 2021. Just as the fast spread of epidemics may be controlled if acting on a timely fashion, infodemics may also be mitigated. However, there are challenges that add an additional burden in management of pandemics, and therefore there is an urgent need to educate the population and implement training programs for healthcare workers aiming to efficiently manage infodemics. The objective of this special paper is to describe the challenges for managing health infodemics in COVID-19 times.